What Are the Links of Prostate Cancer with Physical Activity and Nutrition? : A Systematic Review Article - Joanna KRUK; Hassan ABOUL-ENEIN (Tehran University of Medical Sciences, 2016)
Background: Prostate cancer (PCa) is the second most common malignancy in men worldwide. The purpose of this study was to provide a brief synthesis the current knowledge for the effects of physical activity (PA) and nutrition on PCa risk. Methods: A systematic review of English languages reviews, meta-analysis, and original articles published from 2009 to 2015 extracted from the following websites: MEDLINE, Web of Science, Health Source, Science Direct, and their references. Results: The review of the literature led to the selection of 12 review or meta-analysis studies and 15 lately published observational studies. Most of studies reported relationship of recreational and occupational PA and vegetables, fruits, vitamins, red/processed meats, and fats consumption with risk of PCa. Decreased risk for PCa associated with exercise was reported in seven of the ten articles on this topic. The inverse association of vegetables and/or fruit intake with PCa risk was reported in eight of 13 papers. The effect of meat/fat intake on PCa was estimated in four articles finding increased risk. There was heterogeneity between studies, and findings are inconsistent. Conclusion: Physical activity does not significantly reduce the risk of PCa; however, vigorous exercise may reduce the risk of aggressive tumor. Besides, there is a lack of definitive evidence supporting the preventive role of diet against PCa. Due to many other benefits of regular moderate-vigorous PA and a diet high in vegetables and fruits and low in red/processed meats and fats, these lifestyle patterns may be recommended.